Analysis of Musculoskeletal Disorder Due To Working Postures via Dual Camera Motion Capture System - Ngali, Zamani; Jemain, Noratika Budi; Chang Ann, Wee; Abdol Rahman, Mohd Nasrull; Kaharuddin, Muhammad Zulhilmi; Khairu Razak, Siti Badriah (International Journal of Integrated Engineering, 2018)
Ergonomic are known as the study of work. It helps the worker to fit with the environment of the workplace for example the tools, equipments and the work station. Poor ergonomic practice can affect the performance of the worker and the quality of the product besides can cause loss to the company. This study have three main purpose which is to establish the optimal set up of the dynamic RULA analysis in UTHM, to compare the performance of static RULA analysis with the current dynamic RULA analysis and to identify the effect of current working posture to the musculoskeletal disorder of the university. The ergonomic tools that are use in this study are Cornell Musculoskeletal Discomfort Questionnaire (CMDQ) and Rapid upper limb assessment (RULA). Besides that, motion captures system and Kinect camera is use for 3D dynamic RULA analysis. Besides that, 2D static analysis and 3D dynamic analysis must run the experiment and record the video of the subject motion simultaneously to ensure the similarity in terms of result obtain. Thus, this research finds that the 3D dynamic analysis is more accurate compare with the 2D static analysis. This can be proved by comparing the length of the joint point of 2D static analysis and 3D dynamic analysis with the actual length. 3D dynamic method provided 3 axes while the other method only provided 2 axes. Besides that, 3D dynamic method are analyze by the program while 2D static method are analyze manually by the user that not entirely accurate. The result for comparing the performance of the 2D static analysis and 3D dynamic analysis shows that the respondent 1 and 2 have high risk to get neck pain based on the 3D dynamic analysis RULA score. CMDQ analysis shows that the body part of respondent 1 and 2 that are most probably affected by the MSD is leg.Â